Healing Transgenderism After Surgical Detransition Through Cannabidiol, Magnetic Acupuncture and Neutrons – Theoretical and Practical Prospects - Lavin, Claire; Pirot, Florent (British Journal of Healthcare and Medical Research, 2025)
There are promising yet unexplored pathways for healing transgender people who detransitioned through a combination of cannabidiol, surgery, magnetic acupuncture and neutrons. The pattern behind transgenderism is explored again through a review of the existing literature showing the links with internal contamination with alpha emitters. This contamination can be removed through magnetic acupuncture, neutron treatment (with fission) or a combination of both. Non-magnetic acupuncture also helps neurologically. It is argued that the proven stem cell boost and stem cell migration effect of cannabidiol can be used to restore the primitive organs.